2015
DOI: 10.15639/teflinjournal.v19i1/42-56
|View full text |Cite
|
Sign up to set email alerts
|

The Interactional Approach to the Teaching of Writing and Its Implications for Second Language Acquisition

Abstract: Writing is a language skill which is relatively difficult to acquire. A number of efforts have been made to develop the students' writing skill, among others is by applying different approaches to the teaching of writing. This article discusses the interactional approach to the teaching of writing and its implications for second language acquisition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 15 publications
1
5
0
1
Order By: Relevance
“…The same problems have also been found in Indonesia (e.g. Ariyanti, 2016;Ariyanti and Fitriana, 2017;Lestari, 2008;Husin & Nurbayani, 2017;and Siahaan, 2013).…”
Section: Introductionsupporting
confidence: 68%
“…The same problems have also been found in Indonesia (e.g. Ariyanti, 2016;Ariyanti and Fitriana, 2017;Lestari, 2008;Husin & Nurbayani, 2017;and Siahaan, 2013).…”
Section: Introductionsupporting
confidence: 68%
“…In teaching writing to EFL students, we as teachers cannot always use the writing instruction such as asking the students to write one or two paragraphs regarding a certain topic. Lestari (2008) says that "The stereotype pattern of teaching writing is that the teacher gives a topic and the students write a paper on it". Teaching writing is more than that traditional activity.…”
Section: A Introductionmentioning
confidence: 99%
“…Studies on interactional approach have been conducted by some researchers ( e.g. Jones, Garralda, and Lock, 2006;Lestari, 2008;Ravand and Rasekh, 2011;Ajjawi and Boud, 2017). Jones, Garralda and Lock found that interactional dynamics makes writers have more improvement on their writing.…”
Section: Interactional Approach In Writing Classroommentioning
confidence: 99%
“…In line with Jones, Garralda and Lock (2006), Lestari also found that the interactional approach in the teaching of writing allows students to get beneficial in getting feedback from both teachers and peers. The feedback provision makes the four hypotheses in second language acquisition (the input, monitor, noticing and output hypotheses) work simultaneously during the writing process for better output or the students' final draft of writing can be achieved (Lestari, 2008). Furthermore, Ravand and Rasekh found in their study that it is a need to continue to take a multi-dimensional view of feedback.…”
Section: Interactional Approach In Writing Classroommentioning
confidence: 99%